Pengaruh Kepemimpinan Profetik Terhadap Motivasi Kinerja di Institusi Perguruan Tinggi - Indayanti, Aneu Nandya; Malik, Adam (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
This study aims to determine the positive effect of prophetic leadership on employee performance at the Postgraduate Program of UIN Sunan Gunung Djati Bandung, West Java, Indonesia. This research uses a one-shot pre-experimental case study research design. The data analyzed in this study were obtained from the results of a survey distributed to respondents, by first testing the validity and reliability of the instrument. Based on the results of the data analysis, it shows that prophetic leadership has a significant effect on work motivation. Furthermore, the R. Square value is 0.343, and 65.7% of employee work motivation is influenced by other variables not examined in this study. This study found that overall prophetic leadership has a significant influence on employee work motivation at the Postgraduate institution of UIN Bandung. This indicates the importance of leaders who have prophetic leadership characteristics in improving work motivation and employee performance at the institution. Therefore, the results of this study make an important contribution in the context of educational institution management, highlighting the role of prophetic leadership in motivating employees in higher education.